Photo-crosslinking hydrogel, preparation method and application thereof, radionuclide preparation and application
By introducing dopamine-modified methacrylated gelatin and hyaluronic acid into the photocrosslinked hydrogel, a complex crosslinking network is formed, which solves the problem of insufficient adhesion of existing hydrogels, and achieves instantaneous and firm adhesion on biological tissues and improves the effect of medical applications.
Patent Information
- Application Number
- CN202411652708.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-11-19
AI Technical Summary
The lack of adhesion of existing photocrosslinked hydrogels on biological tissues leads to easy displacement or fall off when used on irregular keloid surfaces, affecting the therapeutic effect of the drug.
By introducing dopamine-modified methacrylated gelatin and o-nitrobenzyl sulfide-modified hyaluronic acid, a complex crosslinking network structure is formed to improve the adhesion of the hydrogel. The hydrogel is crosslinked in various ways under the trigger of light, forming a binding network of permanent covalent bonds and dynamic covalent bonds, enhancing its fatigue resistance and adhesion.
The transient and firm adhesion of photocrosslinked hydrogel on biological tissue is achieved, improving its application effect in the medical field, including the use of radionuclide carriers, patches and hemostatic materials.
Smart Images

Figure BDA0005141370450000061 
Figure BDA0005141370450000062 
Figure HDA0005141370460000011
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of biomedical materials, and more specifically, to a photo-crosslinked hydrogel, a preparation method and application thereof, and a radionuclide preparation and patch. Background Art
[0002] Photocross-linked hydrogel is a gelling system with light as the triggering medium, which is widely used in the biomedical field. First, it can be used as a carrier of radionuclide drugs for embolization therapy. By injecting embolic agents into blood vessels, the blood supply to the lesion site is blocked, thereby reducing or eliminating the lesion. Radionuclides can be embedded in hydrogels as radioactive particles, or locally injected into the tumor site through rare earth ions coordinated with hydrogels. This combination strategy not only "starves" tumor cells by inhibiting blood supply, but also directly kills these cells by releasing radiation energy. However, although hydrogels have obvious advantages as carriers of radionuclides, they still face challenges. For example, the stability of radionuclides is insufficient, which makes them easy to fail rapidly in the body.
[0003] Second, the hydrogel is used as a dressing for keloids. Existing photo-crosslinked hydrogels have poor adhesion and are difficult to fit tightly to the irregular surface of keloids. They are easily displaced or fall off, thus affecting the therapeutic effect of the drug. Third, they can also be used as hemostatic materials. Photo-crosslinked hydrogels can be used to block conventional biological tissue wounds, and can deliver hydrogel precursor solutions to deep, narrow, and irregular wounds after puncture surgery, and use light-triggered gelation to achieve in situ blocking. However, due to insufficient adhesion, the hemostatic effect of these hydrogels is still poor.
[0004] Therefore, there is an urgent need to develop a photo-cross-linked hydrogel with strong adhesion that can achieve instantaneous and firm adhesion to biological tissues to meet the needs of the biomedical field. For example, this hydrogel not only has excellent radionuclide carrier properties, but can also be widely used in medical treatments such as wound sealing and hemostasis. Summary of the invention
[0005] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention proposes a photo-crosslinked hydrogel and a preparation method and application thereof, a radionuclide preparation and a patch. The photo-crosslinked hydrogel provided by the present invention has excellent adhesion, can achieve instantaneous and firm adhesion on biological tissues, and has anti-fatigue performance. The photo-crosslinked hydrogel can meet the needs of medical applications. For example, it can not only be used as a good loading carrier for radionuclides, but also can be used for wound occlusion and hemostasis.
[0006] A first aspect of the present invention provides a photo-crosslinked hydrogel having adhesive properties.
[0007] Specifically, a photo-crosslinked hydrogel (GDHL) with adhesion includes a cross-linked network structure composed of dopamine-modified methacrylated gelatin (GelMADA) and o-nitrobenzyl sulfide photo-trigger-modified hyaluronic acid (HANT).
[0008] The photo-crosslinked hydrogel provided by the present invention undergoes crosslinking in various ways under the triggering of light to form a complex crosslinked network structure, wherein the first crosslinking mode is: a polymer network formed by GelMADA through free radical crosslinking under the triggering of light; the second crosslinking mode is: under the triggering of light, the carbon-sulfur bond at the benzyl position in the HANT molecule breaks to generate active free thiol groups, and Michael addition reaction occurs between the free thiol groups and the double bonds on the GelMADA skeleton to form a polymer network with dynamic carbon-sulfur bonds as crosslinking points; the third crosslinking mode is: a polymer network consisting of disulfide dynamic covalent bonds generated by HANT self-oxidative crosslinking Therefore, the GDHL hydrogel not only has a main skeleton composed of permanent covalent bonds formed by free radical crosslinking of double bonds, but also has an energy dissipation area formed by dynamic covalent bonds embedded in the main skeleton. When a certain pressure is applied to the hydrogel, the dynamic crosslinking points inside the hydrogel effectively dissipate the mechanical force inside the hydrogel through the process of breaking and reforming the covalent bonds, while the long-chain network constructed by the double-bond free radical crosslinking mode can fix the dynamic crosslinking points inside the hydrogel, avoid the displacement of the crosslinking points during the energy dissipation process, further improve the anti-fatigue performance of the hydrogel, and maintain the integrity of the three-dimensional network skeleton of the hydrogel. When the photo-cross-linked hydrogel is further applied to biological tissues, the polar groups on the hyaluronic acid skeleton and the polar environment on the surface of the biological tissues are firmly adhered by forming hydrogen bonds and coordination bonds. At the same time, the mutual penetration between the hyaluronic acid skeleton and the biological tissues can also improve its adhesion to a certain extent. At the same time, synergistic adhesion is achieved through hydrogen bonds, coordination bonds, π-π stacking interactions (chemical effects) and imine covalent bonds (physical effects) brought by dopamine. Under the above combined effects, the adhesion of the hydrogel is greatly improved. The photo-crosslinked hydrogel can be further used as a carrier, for example, to load radionuclides. The prepared radionuclide preparation can be firmly positioned at the lesion site, and the dopamine structure in the hydrogel contains two phenol groups. These phenol groups can form a complex with rare earth ions (radionuclide) through coordination to form a more stable radionuclide preparation to prevent leakage of the nuclide; or a dressing containing radionuclides can be prepared, which can fit tightly on the irregular surface of keloids, so that the therapeutic effect of the radionuclide can be fully exerted and the biocompatibility is good; or it can also be used as a hemostatic material to achieve an excellent hemostatic effect.
[0009] Preferably, in step (1), the degree of dopamine substitution in the dopamine-modified methacrylated gelatin is 14-18%.
[0010] Further preferably, in step (1), the dopamine substitution degree of the dopamine-modified methacrylated gelatin is 16-17%.
[0011] Preferably, in step (2), the mass ratio of the dopamine-modified methacrylic acid gel to the o-nitrobenzyl sulfide photo-trigger-modified hyaluronic acid is (3-6):1.
[0012] Further preferably, in step (2), the mass ratio of the dopamine-modified methacrylic acid gel to the o-nitrobenzyl sulfide photo-trigger-modified hyaluronic acid is (4-5):1.
[0013] If the GelMADA content is too high, it will lead to excessive cross-linking. The high degree of cross-linking will cause the curing process to be too fast, resulting in the inhomogeneity of the hydrogel and difficulty in application. A low GelMADA content will result in an insufficiently dense cross-linked network, and the structural strength and mechanical properties of the hydrogel will be adversely affected.
[0014] A second aspect of the present invention provides a method for preparing a photo-crosslinked hydrogel having adhesiveness.
[0015] A method for preparing a photo-crosslinked hydrogel (GDHL) with adhesion comprises the following steps:
[0016] (1) taking a sodium hyaluronate solution, adding 2-((2-nitrobenzyl)thio)ethane-1-amine and a first condensing agent, mixing, adjusting the pH value to 4-5, and then adding a second condensing agent to perform a first amide reaction to obtain o-nitrobenzyl sulfide photo-triggered hyaluronic acid;
[0017] (2) Dissolving dopamine-modified methacrylated gelatin and o-nitrobenzyl sulfide phototrigger-modified hyaluronic acid in a solvent respectively to obtain a solution containing dopamine-modified methacrylated gelatin and a solution containing o-nitrobenzyl sulfide phototrigger-modified hyaluronic acid, then mixing the two solutions, adding a photoinitiator to obtain a hydrogel precursor solution, and subjecting the solution to photocuring to obtain the photocross-linked hydrogel.
[0018] Preferably, in step (1), the temperature of the first amide reaction is 20-30° C., and / or the time of the first amide reaction is 24-60 h.
[0019] Preferably, in step (1), in step (1), the first condensing agent is 1-hydroxybenzotriazole, and / or the second condensing agent is N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride.
[0020] Preferably, in step (1), the molar ratio of sodium hyaluronate, 2-((2-nitrobenzyl)thio)ethane-1-amine, the first condensing agent, and the second condensing agent is 1:1:1:0.5 to 1:1:1:1.
[0021] Preferably, in step (2), the photocuring time is 1 s-3 min.
[0022] Further preferably, in step (2), the light curing time is 1.5 s-1 min.
[0023] Preferably, in step (2), the photoinitiator is lithium phenyl (2,4,6-trimethylbenzoyl) phosphate (LAP).
[0024] Preferably, in step (2), the solvent is phosphate buffered saline (PBS).
[0025] Preferably, in step (2), the solid content of the hydrogel precursor solution is 4-8%.
[0026] Preferably, in step (2), the method for preparing the dopamine-modified methacrylated gelatin comprises the following steps: mixing dopamine hydrochloride and methacrylated gelatin, and obtaining the dopamine-modified methacrylated gelatin through a second amide reaction.
[0027] Preferably, the temperature of the second amide reaction is 20-30° C., and / or the time of the second amide reaction is 10-24 h.
[0028] Preferably, the methacrylated gelatin is activated before mixing, and the activation step comprises: first dissolving the methacrylated gelatin in a buffer solution, then adding 1-ethyl-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide, and mixing at 20-30° C. for 2-8 minutes.
[0029] Preferably, the buffer solution is a phosphate-buffered saline (PBS) solution, and / or the pH value of the buffer solution is 4-6.
[0030] Preferably, after the amide reaction, post-treatment is performed, and the post-treatment sequentially includes dialysis and drying.
[0031] Further preferably, the post-treatment sequentially comprises dialysis with water for 2-5 days and then freeze-drying.
[0032] Preferably, the dialysis uses a dialysis bag with a molecular weight cut-off of 10,000-16,000 Da.
[0033] The third aspect of the present invention provides a use of a photo-crosslinked hydrogel having adhesiveness.
[0034] Application of an adhesive photo-crosslinked hydrogel in the preparation of a medical carrier, a hemostatic material, a dressing, a wearable device or a sensor.
[0035] A radionuclide-containing preparation comprises a radionuclide and a carrier, wherein the radionuclide is loaded on the carrier, and the carrier is the photo-crosslinked hydrogel with adhesion.
[0036] A radionuclide-containing patch comprises a radionuclide and the photo-crosslinked hydrogel with adhesiveness.
[0037] A hemostatic material comprises the photo-crosslinked hydrogel having adhesiveness.
[0038] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0039] The photo-crosslinked hydrogel with adhesiveness provided by the present invention comprises a crosslinked network structure composed of dopamine-modified methacrylated gelatin (GelMADA) and o-nitrobenzyl sulfide photo-trigger-modified hyaluronic acid (HANT), which is not only injectable and can gel after being triggered by light, but also improves the adhesiveness of the hydrogel by introducing dopamine, and further improves the adhesiveness of the hydrogel by introducing dynamic covalent bonds such as carbon-sulfur bonds and disulfide bonds, while giving it better energy dissipation capacity, and while improving its mechanical properties, it also enables the hydrogel to withstand greater deformation and maintain better elasticity, and has strong anti-fatigue performance; in addition, Physical adhesion is achieved through imine covalent bonds, and chemical adhesion is achieved through various chemical reactions of the photo-induced hydrogel, hydrogen bonds, coordination bonds, and π-π stacking interactions. On the one hand, physical viscosity ensures that the photo-crosslinked hydrogel produces instant adhesion at the moment of contact with biological tissue, thereby ensuring that the photo-crosslinked hydrogel is not easily de-adhesive due to external impact; on the other hand, chemical adhesion requires a corresponding reaction time to produce adhesion. Therefore, after the photo-crosslinked hydrogel contacts the biological tissue, the two gradually bond in the form of chemical bonds, thereby firmly anchoring the photo-crosslinked hydrogel on the tissue surface and providing long-term adhesion. The present invention combines the characteristics of fast but weak physical adhesion with the characteristics of slow but strong chemical adhesion, realizes physical-chemical synergistic enhancement of adhesion, constructs a photo-crosslinked adhesive with instantaneous and firm adhesion, and realizes firm adhesion with biological tissue. The photo-crosslinked hydrogel can be further used as a carrier, for example, after loading the radionuclide, it can be stabilized at the lesion site, or a dressing containing the radionuclide can be prepared, which fits tightly on the irregular keloid surface with good biocompatibility, so that the therapeutic effect of the radionuclide can be fully exerted, or it can also be used as a hemostatic material to achieve excellent in situ blocking and hemostasis. In addition, when the hydrogel is used as a carrier to incorporate radionuclide particles or to form a coordination compound with the ions of the radionuclide, the dopamine structure contains two phenol groups, which can form a complex with the rare earth ions through coordination to form a more stable radionuclide preparation to prevent the leakage of the nuclide. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 The scanning electron microscope (SEM) images of GDHL, GDL and HH hydrogels prepared in Example 1 of the present invention are shown;
[0041] Figure 2 This is a graph showing the rheological properties test results of the GDHL hydrogel prepared in Example 1 of the present invention;
[0042] Figure 3 This is a comparison chart of the lap shear test results of the GDHL hydrogel and fibrin glue prepared in Example 1 of the present invention;
[0043] Figure 4 This is a graph showing the biological tissue adhesion test results of the GDHL hydrogel prepared in Example 1 of the present invention;
[0044] Figure 5 This is a result diagram of the labeling efficiency of the GDHL hydrogel loaded with radionuclides prepared in Example 1 of the present invention;
[0045] Figure 6 This is a graph tracking the stability of the RENP-incorporated GDHL hydrogel prepared in Example 1 of the present invention in mice;
[0046] Figure 7 This is a graph showing the test results of the blocking effect of the GDHL hydrogel prepared in Example 1 of the present invention on kidney puncture wounds. DETAILED DESCRIPTION
[0047] In order to make the technical scheme of the present invention more clearly understood by those skilled in the art, the following embodiments are listed for illustration. It should be pointed out that the following embodiments do not limit the protection scope of the present invention.
[0048] Unless otherwise specified, the raw materials, reagents or devices used in the following examples can be obtained from conventional commercial sources or by existing known methods.
[0049] Parameters and reagents specifically used in the embodiments and comparative examples of the present invention are as follows:
[0050] Da: The unit of weight-average molecular weight of biological macromolecules (such as proteins, nucleic acids, etc.), which is equivalent to the mass of 24,783 hydrogen atoms.
[0051] Preparation method of PBS solution (pH=5): Use NaOH solution to adjust 0.2 mol / L sodium dihydrogen phosphate solution to pH=5.
[0052] Example 1
[0053] A photo-crosslinked hydrogel (GDHL) with adhesiveness comprises a crosslinked network structure consisting of methacrylated gelatin modified with dopamine and hyaluronic acid modified with o-nitrobenzyl sulfide phototrigger.
[0054] The preparation method of the above-mentioned photo-crosslinked hydrogel (GDHL) having adhesiveness comprises the following steps:
[0055] (1) Preparation of dopamine-modified methacrylated gelatin (GelMADA): Dissolve methacrylated gelatin GelMA in a PBS solution at pH = 5 to form a uniform and transparent solution. Then add EDC (3.8 mmol) and NHS (3.9 mmol) and stir at room temperature for 5 min. Add dopamine hydrochloride (3.9 mmol) to the reaction flask in batches, and stir the reaction mixture at room temperature. After the reaction is completed, the reaction mixture is placed in a dialysis bag (14000 Da), dialyzed with deionized water for three days, and freeze-dried to obtain GelMADA as a brown foamy solid. 1 H NMR nuclear magnetic resonance hydrogen spectrum shows that: the multiple peaks at δ = 2.8ppm are the peaks of the benzylic methylene of dopamine Hc, the single peak at δ = 3.12ppm is the peak of Hd on the gelatin molecule, and the double peaks at δ = 5.34ppm are the peaks of Hb on GelMADA, indicating that methacrylated gelatin is modified by dopamine. After calculation, the DA substitution degree of GelMADA is about 16.4%. The MALDI-TOF mass spectrometry test results show that the weight average molecular weight of GelMADA is about 24783Da.
[0056] The above GDHL synthesis route is as follows:
[0057]
[0058] (2) Preparation of o-nitrobenzyl sulfide photo-trigger-modified hyaluronic acid (HANT):
[0059] Sodium hyaluronate (HA) was dissolved in deionized water to form a uniform, transparent solution. 2-((2-nitrobenzyl)thio)ethyl-1-amine (NT) (1 mmol) and 1-hydroxybenzotriazole (HOBT) (1.5 mmol) were dissolved in dimethyl sulfoxide and added dropwise to the reaction flask. After the reaction mixture was stirred at room temperature, the pH value of the reaction solution was adjusted to about 4.5. At this time, N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride (EDC) (1.56 mmol) was dissolved in dimethyl sulfoxide and added dropwise to the reaction system. After the reaction mixture was stirred, the reaction solution was placed in a dialysis bag (molecular weight cutoff 14000 Da) and dialyzed in a deionized water solution containing 0.1 mol / L NaCl at a pH of 3.5. Subsequently, it was placed in deionized water for continued dialysis, and the dialysate was replaced every 3 hours during the dialysis process. After the dialysis was completed, the mixed solution in the dialysis bag was placed in a centrifuge tube and freeze-dried in a light-proof state. The white flocculent product was collected, and the results of H NMR characterization showed that its NT substitution degree was about 19.5%.
[0060] The above-mentioned HANT synthesis route is as follows:
[0061]
[0062] (3) GelMADA (50 mg) and HANT (10 mg) were dissolved in 500 μL PBS solution. After the GelMADA solution and the HANT solution were fully mixed, LAP (10 mg / mL) was added thereto and stirred at room temperature to obtain a GDHL hydrogel precursor solution (solid content 6%, wherein the weight ratio of GelMADA:HANT = 5:1). The above mixture was placed under an ultraviolet lamp (365 nm, 40 mW / cm 2 ) and quickly solidified into gel to form GDHL hydrogel.
[0063] The preparation process of GDHL hydrogel involves multiple cross-linking modes. The first cross-linking mode is: a polymer network formed by GelMADA through free radical cross-linking under light triggering; the second cross-linking mode is: under light triggering, the carbon-sulfur bond at the benzyl position in the HANT molecule breaks to generate active free thiol groups, and Michael addition reaction occurs between the free thiol groups and the double bonds on the GelMADA skeleton to form a polymer network with dynamic carbon-sulfur bonds as cross-linking points; the third cross-linking mode is: a polymer network (HH) composed of disulfide dynamic covalent bonds generated by HANT's own oxidative cross-linking, thus forming a complex cross-linked network structure of GDHL hydrogel.
[0064] Example 2
[0065] A photo-crosslinked hydrogel, which is different from Example 1 in that the DA substitution degree of GelMADA is replaced by 18%. 2 ) and the mixed solution was quickly solidified under the condition of 1% DA, and the GDHL hydrogel was successfully prepared. Increasing the DA substitution degree to 18% helps to reduce the cross-linking time of the material and improve the formation efficiency and curing uniformity of the hydrogel.
[0066] Example 3
[0067] A photo-crosslinked hydrogel, which is different from Example 1 in that the DA substitution degree of GelMADA is replaced by 14%. 2 ) and the mixed solution was quickly solidified under 4% DA, and the GDHL hydrogel was successfully prepared. The cross-linking degree of the hydrogel with a lower DA substitution degree (14%) was moderate, which helped to improve the stability and overall structural integrity of the hydrogel.
[0068] Example 4
[0069] A photo-crosslinked hydrogel, which is different from Example 1 in that the weight ratio of GelMADA:HANT is 6:1. The results show that a hydrogel with a good degree of crosslinking is successfully obtained at this weight ratio.
[0070] Example 5
[0071] A photo-crosslinked hydrogel, which differs from Example 1 in that the weight ratio of GelMADA:HANT is 3:1. The results show that a hydrogel with excellent crosslinking degree is successfully prepared at this ratio.
[0072] Comparative Example 1 (Increasing DA Substitution Degree)
[0073] A photo-crosslinked hydrogel, which differs from Example 1 in that the DA substitution degree of GelMADA is replaced with 20%. Compared with Example 1, too high DA substitution degree leads to aggregation or interaction of materials to form an uneven hydrogel, which exhibits an uneven gelation morphology during the curing process and is difficult to apply.
[0074] Comparative Example 2 (lowering DA substitution degree)
[0075] A photo-crosslinked hydrogel, which differs from Example 1 in that the DA substitution degree of GelMADA is replaced by 13%. The results show that insufficient dopamine content greatly reduces the porosity or crosslinking degree of the hydrogel.
[0076] Comparative Example 3
[0077] A hydrogel (HH), the preparation method of which is:
[0078] The HANT prepared in Example 1 was added to 1 mL of PBS solution, and the HANT and PBS solution were stirred at a moderate speed to ensure that the HANT was completely dissolved and a uniform solution was formed. After completing the above steps, the prepared HANT solution was transferred to an appropriate curing mold. Then, an ultraviolet lamp (wavelength 365 nm, power 40 mW / cm 2 ) irradiate the HANT solution under the above mold to solidify it into glue.
[0079] Comparative Example 4
[0080] A hydrogel (GDL), the preparation method of which is:
[0081] Prepare a 10% (w / v) gelatin solution by dissolving gelatin in deionized water at about 40°C and stirring until completely dissolved. Add glutaraldehyde to the solution and mix thoroughly. Pour the solution into a mold for the crosslinking process. Maintain crosslinking under appropriate conditions for 24 hours. After gelation, remove the hydrogel from the mold. Wash thoroughly with deionized water to remove residual crosslinking agent and unreacted components.
[0082] Comparative Example 5
[0083] Gelatin-dextrin hydrogel (GDH), the preparation method thereof is as follows:
[0084] Dissolve gelatin in deionized water to prepare a 10% (w / v) gelatin solution, and stir at 40°C until completely dissolved. Dissolve dextrin in deionized water to prepare a dextrin solution of appropriate concentration. Mix the gelatin solution and dextrin solution and stir thoroughly. Add an appropriate amount of glutaraldehyde and continue to stir evenly. Pour the mixed solution into a mold. Let stand at an appropriate temperature for 12-24 hours to complete the gelation process. Remove the hydrogel from the mold. Wash the gel with deionized water to remove unreacted substances.
[0085] Comparative Example 6
[0086] Methacrylated gelatin (GL), the preparation method thereof is as follows:
[0087] GelMA (60 mg) and LAP (1 mg) were dissolved in 900 μL and 100 μL PBS solutions respectively, and ultrasonically heated at 50°C to dissolve to form a uniform and transparent solution. The GelMA solution and the LAP solution were mixed together, stirred evenly, and then placed under a UV lamp to solidify into a gel, thereby obtaining a GL hydrogel with a solid content of 6%. GelMA was prepared by aminolysis reaction of gelatin and methacrylic anhydride.
[0088] Comparative Example 7
[0089] Gelatin-hyaluronic acid hydrogel (GHL), the preparation method thereof is as follows:
[0090] GelMA (50 mg), HANT (10 mg) and LAP (1 mg) were dissolved in 400 μL, 500 μL and 100 μL PBS solutions respectively, and dissolved by ultrasonic heating at 50°C to form a uniform and transparent solution. The GelMA solution, HANT solution and LAP solution were mixed together and stirred to make them uniform. The mixed solution was placed under ultraviolet light to solidify into a gel, and a GHL hydrogel with a solid content of 6% was obtained, wherein mGelMA:mHANT=5:1.
[0091] Application effect test
[0092] The GDHL hydrogel prepared in Example 1 was subjected to the following performance tests.
[0093] 1. Appearance and shape
[0094] The morphology of GDHL, GDL and HH hydrogels was characterized by SEM. Figure 1 As shown in A, B, and C, it was found that the GDHL hydrogel had dense cross-linking inside, with pore sizes varying and showing a cross-distribution characteristic. Moreover, compared with traditional single cross-linked network hydrogels (GDL, HH), the GDHL hydrogel had a denser pore distribution and a relatively larger cross-linking density.
[0095] After confirming that the GDHL hydrogel system has good gelation performance, its single-point gelation ability was further tested. Specifically, it was gelled in heavy water under light irradiation, and the heavy water around the GDHL hydrogel was characterized by nuclear magnetic resonance. The results showed that there were no ungelled monomer fragments in the aqueous solution, and no free GDHL hydrogel fragments were found, proving that the GDHL hydrogel has good single-point gelation performance.
[0096] 2. Rheological properties
[0097] The GDHL hydrogel precursor solution of Example 1 was evenly applied on the lower plate of the rotational rheometer. The in-situ UV curing gelation process was tested in the time scanning oscillation mode. The test conditions were as follows: UV light source wavelength 365nm, light power density 40mW / cm 2 The gel point is the intersection of the G′ (storage modulus) and G″ (loss modulus) curves, and the final gel modulus is the average modulus when the G′ curve tends to equilibrium.
[0098] Results Figure 2 With the extension of illumination time, G′ and G″ of GDHL hydrogel gradually increased, reaching the gelation point 1.5s after illumination, when G′ and G″ intersected, proving that the hydrogel had shown solid viscoelasticity at this time. With continued illumination, G′ and G″ continued to increase, and the final gelation modulus of G′ could reach 4845.7Pa. Among them, Figure 2 Where G′ and G″ represent the storage modulus and loss modulus of the material, respectively. The storage modulus represents the elastic energy stored in the material when strain is applied, and the loss modulus represents the energy dissipated by the material when strain is applied. Time represents time. When the compressive strain is 50%, the compressive strength of GDHL hydrogel is 51.5 kPa and the Young's modulus is 17.7 kPa. These results show that GDHL hydrogel has excellent mechanical properties, which ensures that GDHL hydrogel can withstand higher mechanical loads and deformations. In addition, the energy dissipation of GDHL hydrogel rises sharply to 102.34 kJ / m 3 This is mainly due to the dynamic covalent bonds in the hydrogel. The mechanical force acting on the hydrogel is dissipated by the breaking of the dynamic CS bonds and SS bonds, enabling it to withstand greater pressure and maintain good elasticity after the pressure is removed, with excellent anti-fatigue performance. In addition, the characterization of the shear thinning properties of the GDHL hydrogel precursor solution shows that the viscosity of the GDHL hydrogel precursor solution gradually decreases with the increase of the shear rate, indicating that the intermolecular forces within the hydrogel precursor solution gradually weaken under the action of the shear force. This shows that the GDHL hydrogel has good injectability, which is conducive to its injection in subsequent biological applications.
[0099] Under 365nm ultraviolet light irradiation with the same optical power density, the gelation points of single cross-linking mode hydrogels HH, GDH, and GDL are 2.8s, 2.5s, and 15.63s, respectively, indicating that GDHL exhibits a faster gelation speed than the single cross-linking mode hydrogels HH, GDH, GDL, and GL. Compared with the commercial UV-curable hydrogel GelMA (GL), the GDHL hydrogel also exhibits a faster gelation rate and higher mechanical strength. The GL hydrogel can reach the gelation point at 2.82s of light irradiation, which is nearly twice as slow as the GDHL hydrogel, and its final modulus is only 1 / 6 of that of the GDHL hydrogel. This result shows that the introduction of HANT greatly improves the gelation properties of the GDHL hydrogel.
[0100] The gelation rate of GDHL hydrogel is much faster than that of GDL hydrogel, which may be caused by the introduction of dopamine. The benzene ring in dopamine is a rigid skeleton. After the introduction of flexible molecular chains, it will form a stacking structure in the hydrogel precursor solution. The resulting reduction in compatibility may cause a tiny phase separation structure inside the hydrogel precursor solution. This effect will reduce the gelation efficiency of the GDL hydrogel precursor solution and thus prolong its gelation time. After the addition of HANT macromolecules, the large number of polar groups on the surface of the macromolecules can not only interact closely with the aqueous solution, but also shorten the distance between molecules, weaken the phase separation caused by dopamine, and thus improve the gelation efficiency of GDHL. HH and GDH hydrogels are mainly formed by oxidation reactions and Michael addition reactions, and their reaction rates are significantly lower than those of photo-induced free radical addition. Therefore, their gelation rates are also relatively slow. In addition, compared with the single cross-linking mode hydrogels, GDHL hydrogel also exhibited higher mechanical strength, and its final modulus was 7.5, 4.0 and 88 times that of HH, GDH and GDL hydrogels, respectively, further proving the advantage of hybrid cross-linked hydrogel in gelation performance.
[0101] 3. Tissue Adhesion
[0102] The tissue adhesion of GDHL hydrogel was evaluated by pig skin lap shear test. Specifically, two pieces of pig casings were adhered to two glass slides with cyanoacrylate glue. After they were fixed, the GDHL hydrogel precursor solution was transferred and evenly applied to the surface of the pig casings. Another glass slide covered with pig casings was placed on the glass slide so that the pig casings on the two glass slides adhered together. After pressing, it was placed under a UV lamp (365nm, 40mW / cm 2) for 5 minutes to solidify the hydrogel between the pig casings into glue and adhere together. The prepared samples were tested using a tensile testing machine and the breaking force was recorded. Fibrin glue and GHL hydrogel were tested using the same method and test parameters to calculate the bonding strength. For comparison, this experiment also selected the unmodified dopamine hydrogel GHL and the commercially available medical glue fibrin glue (Fibrin glue) for comparison. Figure 3 The experimental results show that the adhesion strength of GDHL hydrogel can reach 49kPa, which is much higher than GHL hydrogel (24.3kPa) and fibrin glue (12.7kPa). Figure 3 Tissue adhesive strength refers to tissue adhesive strength.
[0103] 4. Used as a medical dressing
[0104] In order to explore the application effect of GDHL hydrogel as a medical dressing, GelMADA was dissolved in 400 μL of PBS solution to ensure its complete dissolution. A magnetic stirrer was used to stir until the solution was uniform. At the same time, HANT was dissolved in 500 μL of PBS solution and stirred with a magnetic stirrer until the solution was uniform. The GelMADA solution was mixed with the HANT solution, placed in a sterile container, stirred at room temperature with a magnetic stirrer, and then LAP photoinitiator was added to the mixed solution, and then slowly added 32 P solution (Na2HPO4) and Eosin Y (eosin Y) for staining. This process should be performed on a radioactive operating table and avoid bubbles. Transfer the mixture to the mold. Place the mold under ultraviolet light (365nm, 40mW / cm 2 ) and photocured to obtain 32 P-GDHL hydrogel. The GDHL hydrogel precursor solution was coated on pig skin tissue and formed into a hydrogel in situ under UV light. 32 Adhesion of P-GDHL hydrogel. Figure 4 The results showed that before immersion, 32 P-GDHL hydrogel can firmly adhere to pig skin tissue without falling off during stretching, bending, twisting and flushing with running water at different pressures; then, the pig skin tissue adhered with hydrogel was immersed in PBS solution, and it was found that after about 48 hours of immersion, GDHL hydrogel can still adhere to the pig skin surface, indicating that GDHL hydrogel has strong tissue adhesion. This proves 32P-GDHL hydrogel has excellent mechanical properties and elasticity, and can fit tightly to the biological tissue to be treated (such as keloids), providing effective local fixation, reducing the displacement or shedding of the dressing, and improving the stability and effectiveness of the treatment. In addition, hyaluronic acid has moisturizing and antibacterial properties. 32 P-GDHL hydrogel dressing can also provide certain antibacterial effects during the treatment process, reduce the risk of infection, and promote the regeneration of damaged skin. It can be used as a medical dressing for the treatment of keloids, etc. Figure 4 In the figure, before soaking refers to before soaking, after soaking refers to after soaking, Original state refers to original state, Stretching refers to stretching, Twisting refers to twisting, Folding refers to bending, and Water flow refers to water flow.
[0105] The above experimental results all show that after the introduction of dopamine, the adhesion between the hydrogel and the tissue is significantly improved; the introduction of HANT greatly improves the adhesion of the hydrogel, which is because the large number of polar groups such as hydroxyl groups on the hyaluronic acid molecules can produce adhesion with the tissue through hydrogen bond interactions.
[0106] 5. Used as a carrier of radionuclides
[0107] Will 177 LuCl3 solution was added to the physiological saline containing the GDHL hydrogel of Example 1, and ultrasonicated at 50°C for 30 min, and then the pH value was adjusted to 12-13 with sodium hydroxide solution, followed by centrifugation at 5000 rpm for 5 min. After removing the supernatant, the mixture was washed and centrifuged three times alternately with deionized water and physiological saline to remove free 177 LuCl3, finally obtained 177 Lu-GDHL radiolabeled hydrogel. 177 Lu-GDHL radiolabeled hydrogel is used as a radioembolic agent in the treatment of liver cancer. The process is as follows: first, an anesthetic is injected into the abdominal cavity and the rabbit is fixed on a rabbit board; then the right thigh is shaved, the skin and muscles are cut, and the femoral artery is found and exposed; then a small incision is made in the femoral artery with scissors, and the sheath is introduced into the femoral artery. Then, the catheter and guide wire are introduced into the sheath, and the catheter is inserted into the hepatic artery. 177 The Lu-GDHL radiolabeled hydrogel was injected into the artery via a catheter, and the diffusion of the material in the body was monitored by digital subtraction angiography (DSA) and fluorescence imaging.
[0108] Under the monitoring of digital subtraction angiography (DSA) and fluorescence imaging, the results showed that177 After Lu-GDHL radiolabeled hydrogel embolization, the hydrogel can be accurately injected into the hepatic artery and can be clearly seen in imaging. 77 Lu-GDHL radiolabeled hydrogel forms local concentration in the liver tumor area, has stable distribution in the tumor, and has low radioactivity leakage rate. 177 The stability of Lu radiolabeling exceeds 95% (see Figure 5 ).because 177 Due to the sustained release of Lu, the tumor area can maintain a high radioactive dose for a long time. This continuous radioactive irradiation can enhance the killing effect on tumor cells while relatively reducing radiation damage to normal tissues. The above results show that the dynamic covalent bonds of the hydrogel can form a strong chemical interaction in the tumor tissue environment, promoting the adhesion between the hydrogel and the tumor tissue. 177 Lu can be stably incorporated into the hydrogel network, reducing the leakage of radionuclides, which further means 177 Lu-GDHL hydrogel can form local concentration in the tumor area and improve the targeted treatment effect. In addition, when the hydrogel prepared in the embodiment of the present invention is used as a carrier to form a coordination compound with the ions of the radionuclide, the dopamine structure contains two phenol groups, which can form a complex with the rare earth ions through coordination to form a more stable radionuclide preparation to prevent nuclide leakage.
[0109] In order to track the existence status of the hydrogel implanted in the body, double-layer rare earth nanoparticles NaYbF4: 2% Er, 2% Ce@NaYF4 (RENP) were used. The particle size of the rare earth nanoparticles is about 35nm, the excitation light wavelength is 980nm, and the emission peak is at 1550nm. Since the emission wavelength of RENP is in the near-infrared region, compared with RENP emitting in the visible light region, it can reduce the influence of biological tissue on light absorption and scattering, which is suitable for high-resolution in vivo imaging. Therefore, RENP was incorporated into the GDHL hydrogel precursor solution and in situ cured to form a hydrogel. The hydrogel was implanted into the back of mice by subcutaneous injection and in situ gelation was performed by ultraviolet light. The results showed that Figure 6 , 7 hours after implantation in vivo, the GDHL hydrogel still adhered firmly in place without movement or diffusion, proving that the GDHL hydrogel has good adhesion and stability in vivo.
[0110] 6. Hemostatic performance
[0111] The hydrogel prepared in Example 1 was applied to the occlusion of kidney puncture wounds, specifically to evaluate the hemostatic performance of GDHL hydrogel on rabbit kidney puncture wounds. First, a puncture needle was used to puncture the lower end of the rabbit kidney to create a bleeding wound; then a light-curing needle was inserted into the bottom of the needle channel, the ultraviolet light source was turned on, and the GDHL hydrogel precursor solution was injected at the same time; as the light-curing needle was slowly withdrawn, a dense GDHL hydrogel occluding matrix was formed inside the puncture needle channel, the needle channel was blocked, and the bleeding stopped. The amount of blood loss of GDHL hydrogel, fibrin glue and the control group is shown in Figure 2. Figure 7 As shown in the figure, by statistically analyzing the hemostasis time and bleeding volume during the occlusion process, it was found that GDHL hydrogel can completely occlude bleeding wounds within 34 seconds, and its hemostasis time is basically the same as that of the commonly used fibrin glue (37 seconds) in clinical practice. For the blank control group without any hemostasis measures, complete hemostasis takes about 135 seconds. In addition, the amount of bleeding in the GDHL hydrogel occlusion experimental group was significantly reduced compared with that of fibrin glue. This result may be caused by the hemostasis characteristics of the light-curing needle. Since the light-curing needle is inserted into the bottom of the needle channel to stop bleeding, this method can block the bleeding wound in time, thereby avoiding a large amount of blood gushing out along the needle channel. Fibrin glue mainly blocks the needle hole at the top of the needle channel, that is, the surface of the kidney wound. During the occlusion process, fibrinogen and thrombin need to be mixed. This cumbersome operation process inevitably increases the amount of bleeding during the hemostasis process. Therefore, compared with GDHL hydrogel, the fibrin glue control group has a larger amount of bleeding. These results show that GDHL hydrogel has excellent hemostatic properties and can seal wounds in a short period of time while also greatly reducing bleeding. Figure 7 In the table, Bleeding weight refers to the amount of bleeding and Control refers to the control group.
Claims
1. A photo-crosslinked hydrogel, characterized in that: It includes a cross-linked network structure consisting of dopamine-modified methacrylated gelatin and o-nitrobenzyl sulfide photo-trigger-modified hyaluronic acid.
2. The photo-crosslinked hydrogel according to claim 1, characterized in that The degree of dopamine substitution in the dopamine-modified methacrylated gelatin is 14-18%.
3. The photo-crosslinked hydrogel according to claim 1, characterized in that The mass ratio of the dopamine-modified methacrylic acid gel to the o-nitrobenzyl sulfide photo-trigger-modified hyaluronic acid is (3-6):
1.
4. A method for preparing a photocrosslinked hydrogel, characterized in that: The steps include: (1) taking a sodium hyaluronate solution, adding 2-((2-nitrobenzyl)thio)ethane-1-amine and a first condensing agent, mixing, adjusting the pH value to 4-5, and then adding a second condensing agent to perform a first amide reaction to obtain o-nitrobenzyl sulfide photo-triggered hyaluronic acid; (2) Dissolving dopamine-modified methacrylated gelatin and o-nitrobenzyl sulfide phototrigger-modified hyaluronic acid in a solvent respectively to obtain a solution containing dopamine-modified methacrylated gelatin and a solution containing o-nitrobenzyl sulfide phototrigger-modified hyaluronic acid, then mixing the two solutions, adding a photoinitiator to obtain a hydrogel precursor solution, and subjecting the solution to photocuring to obtain the photocross-linked hydrogel.
5. The method for preparing the photo-crosslinked hydrogel according to claim 4, characterized in that: In step (1), the temperature of the first amide reaction is 20-30° C., and / or the time of the first amide reaction is 24-60 hours.
6. The method for preparing a photo-crosslinked hydrogel according to claim 4, characterized in that: In step (1), the first condensing agent is 1-hydroxybenzotriazole, and / or the second condensing agent is N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride.
7. The method for preparing a photo-crosslinked hydrogel according to claim 4, characterized in that: In step (2), the photoinitiator is phenyl (2,4,6-trimethylbenzoyl) phosphate lithium salt.
8. The method for preparing a photo-crosslinked hydrogel according to claim 4, characterized in that: In step (2), the solid content of the hydrogel precursor solution is 4-8%.
9. The method for preparing a photo-crosslinked hydrogel according to claim 4, characterized in that: In step (2), the method for preparing the dopamine-modified methacrylated gelatin comprises the following steps: mixing dopamine hydrochloride and methacrylated gelatin, and preparing the dopamine-modified methacrylated gelatin through a second amide reaction.
10. The method for preparing a photo-crosslinked hydrogel according to claim 9, characterized in that: The temperature of the second amide reaction is 20-30° C., and / or the time of the second amide reaction is 10-24 hours.
11. The method for preparing a photo-crosslinked hydrogel according to claim 9, characterized in that: The methacrylated gelatin is activated before mixing, and the activation step comprises: first dissolving the methacrylated gelatin in a buffer solution, then adding 1-ethyl-(3-dimethylaminopropyl) carbodiimide and N-hydroxysuccinimide, and mixing at 20-30° C. for 2-8 minutes.
12. Use of the photocrosslinked hydrogel according to any one of claims 1 to 3 or the photocrosslinked hydrogel prepared by the preparation method according to any one of claims 4 to 11 in the preparation of medical carriers, hemostatic materials, dressings, wearable devices or sensors.
13. A preparation containing radionuclides, characterized in that: The invention comprises a radioactive nuclide and a carrier, wherein the radioactive nuclide is loaded on the carrier, and the carrier is the photo-crosslinked hydrogel according to any one of claims 1 to 3 or the photo-crosslinked hydrogel prepared by the preparation method according to any one of claims 4 to 11.
14. A radionuclide-containing patch, characterized in that: The invention comprises a radioactive nuclide and the photo-crosslinked hydrogel according to any one of claims 1 to 3 or the photo-crosslinked hydrogel prepared by the preparation method according to any one of claims 4 to 11.
15. A hemostatic material, characterized in that: The invention comprises the photo-crosslinked hydrogel according to any one of claims 1 to 3 or the photo-crosslinked hydrogel prepared by the preparation method according to any one of claims 4 to 11.
Citation Information
Patent Citations
Photo-crosslinking injectable nanofiber-hydrogel compound as well as preparation method and application thereof
CN114316162A
Preparation method of injectable bi-crosslinking hydrogel dynamically combined with natural polyphenol
CN114716700A
Composite material used as wound dressing and preparation method thereof
CN115837091A
Double-network hydrogel as well as preparation method and application thereof
CN117924741A
Preparation method of photo-crosslinking hyaluronic acid / polylysine antibacterial adhesive hydrogel
CN117924747A
Cited By
Ultrathin radioactive application for skin cancer treatment and preparation method thereof
CN120983667A